Vector Evaluated Gravitational Search Algorithm Assisted by Non-dominated Solutions in Solving Multiobjective Optimization Problems - Badaruddin, Muhammad; Khairul Hamimah, Abas; Mohd Riduwan, Ghazali (Universiti Malaysia Pahang, 2016)
Previously, non-dominated solutions have been employed to improve the performance of particle swarm optimization (PSO). In this paper, we re-implement the same concept to gravitational search algorithm (GSA). The performance is investigated by solving a set of ZDT test problem. An analysis also is performed by varying the value of initial gravitational constant.